A Satellite Era Warming Hole in the Equatorial Atlantic Ocean. Issue 4 (17th April 2020) - Nnamchi, Hyacinth C.; Latif, Mojib; Keenlyside, Noel S.; Park, Wonsun
Abstract: Observations during the satellite era 1979–2018 only depict small sea surface temperature (SST) trends over the Equatorial Atlantic cold tongue region in boreal summer. This lack of surface warming of the cold tongue, termed warming hole here, denotes an 11% amplification of the mean SST annual cycle. The warming hole is driven by a shoaling of the equatorial thermocline, linked to increased wind stress forcing, and damped by the surface turbulent heat fluxes. The satellite era warming deficit is not unusual during the twentieth century—similar weak trends were also observed during the 1890s–1910s and 1940s–1960s. The tendency for surface cooling appears to reflect an interaction of external forcing, which controls the timing and magnitude of the cooling, with the intrinsic variability of the climate system. The hypothesis for externally forced modulation of internal variability is supported by climate model simulations forced by the observed time‐varying concentrations of atmospheric greenhouse gases and natural aerosols. These show that increased greenhouse forcing warmed the cold tongue and aerosols cooled it during the satellite era. However, internal variability, as derived from control integrations with fixed, preindustrial values of greenhouse gases and aerosols, can potentially cause larger cooling than observed during the satellite era. Large uncertainties remain on the relative roles of external forcing and intrinsic variability in both observations and coupled climate models. Plain Language Summary: The Atlantic cold tongue is a region of locally cooler ocean surface waters that develops just south of the equator in boreal summer, partly reflecting the upwelling of deep cold waters by the action of the southeasterly trade winds. Although there has been considerable global warming since the beginning of global satellite measurements in 1979, there is hardly any surface warming in the Atlantic cold tongue region during 1979–2018. This warming hole is most pronounced in boreal summer. Observations suggest that despite strong heat transfer from the atmosphere to the ocean, the upper ocean may have cooled. Climate model simulations show that variations in external forcing associated with greenhouse gases can cause warming of the cold tongue and aerosols cooling of it. However, model simulations that exclude variations in these external forcing show that the mechanisms internal to the climate system can potentially cause larger cooling than observed during the satellite era. Thus, we attribute the warming hole to a combination of internal variability and external forcing. It must be stressed, however, that understanding the relative roles of internal variability versus external forcing is greatly hampered by large errors in both the observational data sets and climate models. Key Points: Observations show small warming trends over the equatorial Atlantic in boreal summer during the satellite era The small trends are driven by intensified shoaling of the thermocline and damped by the surface turbulent heat fluxes The warming deficit reflects the interactions of intrinsic variability with external forcing